Ecological conditions affect behavioral and morphological trait variability of lake sturgeon (Acipenser fulvescens Rafinesque, 1817) yolk‐sac larvae. (1st December 2017) - Jay, K. J.; McGuire, J. M.; Scribner, K.T.
Summary: The effects of stream environmental conditions on inter individual variability were quantified for lake sturgeon, Acipenser fulvescens (Rafinesque, 1817) yolk sac larvae in the expression of behavioral and morphological traits. Simulated experimental treatments including food availability (brine shrimp), presence of chemosensory predator cues (adult crayfish and odonate larvae), and conspecific density (2 verses 1 larvae) were applied to determine the effects on the duration of time in substrates following hatch and growth from hatch until emergence. In spring 2010, larvae from two full‐sib families were individually placed into 240 mL perforated plastic containers ( n  = 263) with gravel substrate immediately following hatch. Containers were maintained in stream water at ambient temperatures and constant flow (~0.03 m/sec) in 4 m experimental flowing streams. Duration of time (days) each individual remained in the substrate was recorded. Morphological traits including total length (mm), body area (mm 2 ), and yolk‐sac area (mm 2 ) were measured at hatch and at the time of emergence from substrate to compare growth and amount of endogenous yolk reserves used in individuals among experimental treatments. Environmental conditions significantly affected emergence time. Individuals emerged earlier in treatments exposing larvae to chemosensory predator odorants and higher conspecific density. Use of endogenous reserves (yolk‐sac area) at the time of emergence did not differ among treatments. Growth was significantly greater when individuals were provided a food source compared to all other treatments. Quantifying the magnitude and direction of phenotypic responses to environmental conditions is important to understand potential factors affecting survival during early life stages and population viability under conditions of increasing environmental variability.